Vitamin D 25OH Deficiency and Mortality in Moderate to Severe COVID-19: A Multi-Center Prospective Observational Study - Bogliolo, Laura; Cereda, Emanuele; Klersy, Catherine; Stefano, Ludovico De; Lobascio, Federica; Masi, Sara; Crotti, Silvia; Bugatti, Serena; Montecucco, Carlomaurizio; Demontis, Stefania; Mascheroni, Annalisa; Cerutti, Nadia; et al. (Frontiers in Nutrition, 2022)
Introduction Several studies and meta-analyses suggested the role of vitamin D 25OH in preventing severe forms of coronavirus disease 2019 (COVID-19). However, the evidence on the clinical benefits of vitamin D 25OH adequacy in patients hospitalized for COVID-19 remain conflicting and speculative. We aimed to investigate the association between vitamin D 25OH serum levels and mortality in hospitalized patients with moderate to severe COVID-19. Method This prospective observational multicentre study included 361 consecutive patients with moderate to severe COVID-19 admitted to the Italian hospitals involved in the NUTRI-COVID19 trial from March to August 2020. For each patient, serum vitamin D 25OH levels were assessed 48 h since admission and classified as deficient (<20 ng/mL) or adequate (≥20 ng/mL). We built a propensity score for low/adequate vitamin D 25OH levels to balance the clinical and demographic properties of the cohort, which resulted in 261 patients with good common support used for the survival analysis. Results Two Hundred-seventy-seven (77%) of the 361 enrolled patients (207 [57%] males, median age 73 ± 15.6 years) had vitamin D 25OH deficiency. Fifty-two (20%) of the 261 matched patients died during the hospital stay, corresponding to a hazard ratio of 1.18 for vitamin D 25OH deficiency (95% confidence interval: 0.86–1.62; p = 0.29). Discussion The prevalence of vitamin D 25OH deficiency was confirmed to be very high in hospitalized patients with COVID-19. The use of a propensity score demonstrate an absence of significant association between vitamin D deficiency and mortality in hospitalized patients.